In defense of a political union of CARICOM states : a response to the report of the West Indian Commission - Lewis, Patsy (2003)
Looks at the road not travelled by the West Indian Commission : that of a more politically-driven process, with economic integration playing a subordinate role. Examines the renewed interest in political union and presents a vision of an integration process.